2015
DOI: 10.21608/ejnf.2015.105367
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Feeding Sprouted Barley Grains on Rice Straw and Olive Cake on Performance of Goats in Sinai

Abstract: he present experiment was aimed to study the effect of sprouted barley grains (Hordeum vulgare L.) on a mixture of olive cake and rice straw (50:50) as a media without (T2) or with 1% (T3), 2% (T4), or 3% (T5) of urea solutions in comparison with the control Alfalfa, (Medicago sativa). All diets were fed ad libitum for 45 days. The experiment was performed on twenty desert male goats (18 months old) with an initial body weight of 24.34±1.29 kg randomly divided into five equal groups, (4 animals per group). Fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
2
0
0
Order By: Relevance
“…Providing the animal with a concentrates mixture and sprouted maize fodder caused a significant increase in both ruminal ammonia N and TVFA, presumably due to increased micro-organism activity (De Oliveira Franco et al 2017). The same results were demonstrated by a previous study performed with goats, where ammonia N concentration increased as a result of sprouted barley feeding (Helal 2015). Based on those results, we hypothesized that feeding a diet with an increasing substitution rate of maize fodder would increase rumen fermentation, as well as DM and nutrient digestibility.…”
Section: Rumen Parameterssupporting
confidence: 77%
“…Providing the animal with a concentrates mixture and sprouted maize fodder caused a significant increase in both ruminal ammonia N and TVFA, presumably due to increased micro-organism activity (De Oliveira Franco et al 2017). The same results were demonstrated by a previous study performed with goats, where ammonia N concentration increased as a result of sprouted barley feeding (Helal 2015). Based on those results, we hypothesized that feeding a diet with an increasing substitution rate of maize fodder would increase rumen fermentation, as well as DM and nutrient digestibility.…”
Section: Rumen Parameterssupporting
confidence: 77%
“…Dadhich et al (2020) found highly significantly (p<0.01) effect of feeding of hydroponics maize fodder. The increase in rumen ammonia concentration on feeding hydroponics fodder has been reported by Fayed (2011) andHelal (2015).…”
Section: Rumen Ammonia Nitrogen (Nh 3 -N Total Rumen N Tca Precipitab...supporting
confidence: 68%
“…(2019) observed that hydroponic maize fodder had a significant ( p < 0.01) impact on the percentages of DCP% and TDN% in Rathi calves. Helal (2015) noted that the TDN g kg −1 BW and DCP% enhanced significantly ( p < 0.05) using sprouted barley grain in goats.…”
Section: Discussionmentioning
confidence: 89%